Understanding contemporary Islamic crises in the Middle East the issues beneath the surface - Fuller, Graham E. 1937- (Leiden Publications, 2016)
Over the past decade the Middle East has undergone huge geopolitical shifts, including widespread war and violence, the collapse of numerous regimes, a changing American role, a restored Russian presence, and the emergence of ISIS. In this book Graham Fuller addresses the character of these shifts and how they will shape the future of this tumultuous region as well as the role of major outside powers. Fuller firstly focuses on Shari'a law and its appropriate role, if any, in the politics and governance of the Muslim world, thereby further exploring why identity may be the most important factor in examining Middle East politics today. Next he addresses the current Shi'ite-Sunni conflict, not simply by scrutinizing the essentially theological approach found in most Western analysis but also through better understanding the many more extra-religious factors behind the scenes. Finally the author claims that the appearance of ISIS has stretched the perennial phenomenon of Political Islam to the extreme. What, then, does ISIS imply for the future of the Middle East and for Islamist movements in general, not to mention for Muslims' understanding of Islam itself?
Auf dem Umschlag: "LUCIS, Leiden University Centre for the Study of Islam & Society" und "Van Vollenhoven Institute for Law, Governance & Society"
Keywords: Geschichte 2000-1016; Geschichte; Islamisches Recht; Internationale Politik; Naher Osten; Islamische Staaten; Middle East / History / 21st century; Islamic law; IS (Organization); Middle East; 2000-2099; History